2006
DOI: 10.1111/j.1467-7652.2005.00175.x
|View full text |Cite
|
Sign up to set email alerts
|

Design of tomato fruits with reduced allergenicity by dsRNAi‐mediated inhibition of ns‐LTP (Lyc e 3) expression

Abstract: SummaryPlant genetic engineering has the potential to introduce new allergenic proteins into foods but, at the same time, it can be used to remove established allergens. Here, we report the molecular characterization of Lyc e 3, a new tomato ( Lycopersicon esculentum ) allergen, and the efficient down-regulation of its expression in transgenic tomato plants. Ectopic expression of LTPG1 and LTPG2 in Escherichia coli , followed by immunoblotting, verified their IgE reactivity. Subsequently, transgenic tomato pla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
49
0
5

Year Published

2008
2008
2017
2017

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 102 publications
(55 citation statements)
references
References 65 publications
1
49
0
5
Order By: Relevance
“…AB055500]). RNAi is homology dependent, and earlier studies revealed that 90% sequence identity between two nucleotide sequences is sufficient to trigger effective RNA degradation (Schweizer et al, 2000;Le et al, 2006;Chen et al, 2008).…”
Section: Differential Cwinv Deficiency In Tobacco Leaves Caused By Rnmentioning
confidence: 99%
See 1 more Smart Citation
“…AB055500]). RNAi is homology dependent, and earlier studies revealed that 90% sequence identity between two nucleotide sequences is sufficient to trigger effective RNA degradation (Schweizer et al, 2000;Le et al, 2006;Chen et al, 2008).…”
Section: Differential Cwinv Deficiency In Tobacco Leaves Caused By Rnmentioning
confidence: 99%
“…AF506005), primers were designed from the highly homologous sequence region of both sequences (bp 755-1,162 according to LIN8 sequence). In this region, both sequences share 81.9% sequence identity, which is thought to be sufficient to silence both isoforms by a single construct (Le et al, 2006;Chen et al, 2008). A 400-bp cDNA fragment of LIN8 was amplified by PCR using the primers LIN8-5# 5#-caccggtactggaaattggg-3# and LIN8-3# 5#-acaggccattgaaccaattg-3# (nt 755-1,162 of LIN8), and tomato (Solanum lycopersicum) leaf cDNA as a template.…”
Section: Rnai-plasmid Construction and Tobacco Transformationmentioning
confidence: 99%
“…In peanut, the Ara h 2 is one of the most allergic protein present out of 7 allergenic proteins. To remove Lyc e3 from tomato, Le et al (2006) have demonstrated an efficient silencing of Lyc e3, a tomato allergen that encodes a nonspecific lipid transfer protein in the RNAi-silenced tomato plants. Siritungam and Sayre (2003) have reduced the linamarin content, a cyanogenic substance in cassava plants.…”
Section: Allergen and Toxin Eliminationmentioning
confidence: 99%
“…Later nsLTPs have also been identified as allergens in e.g. oranges, tomato, hazelnut, olive tree pollen and cabbage (Tejera et al, 1999;Pastorello et al, 2002;Ahrazem et al, 2005;Le et al, 2006;Palacin et al, 2006). Due to the similarity in structure between nsLTPs from different plants, there is a high rate of cross-reactivity (Egger et al, 2010).…”
Section: The Non-specific Lipid Transfer Proteins Backgroundmentioning
confidence: 99%